COMPARISON BETWEEN ATRAUMATIC RESTORATIVE TREATMENT AND NON-RESTORATIVE TREATMENT FOR CARIES DISEASE CONTROL - de Lima Piccinin Marçal Costa, Bruna; Biscola, Natália; Macedo, Gabriela (Health and Society, 2023)
Non-restorative treatment, along with atraumatic restorative treatment (ART) are considered minimally invasive procedures within dentistry. Non-restorative treatment basically consists of preventing, controlling and reversing the carious lesion and atraumatic restorative treatment (ART) in the removal of carious tissue using manual instruments, promoting remineralization of both enamel and dentin. These techniques are considered as an alternative to control fear and anxiety within Pediatric Dentistry, in patients with behavioral problems, in cases of anxious, non-collaborative children or those with systemic impairments. Thus, the present work turns to a literature review with the objective of comparing Atraumatic Restorative Treatment and Non-restorative Treatment within their indications for long-term caries control, describing the materials that are used and methods used. As a result, we observed the effectiveness of fluoride in its various compositions, the ability to prevent carious lesions using Silver Fluoride Diamine, the regression of lesions through the use of casein and the benefit of ART in reducing dental anxiety and patient discomfort. It is concluded that the type of treatment to be chosen depends on the characteristic and degree of the lesion. In the case of superficial stains, the procedure adopted is non-restorative and in the case of dentinal cavities, ART offers good results.